Experimental study of free convection from vertical tubes with curved extended surfaces - Kim, Donghyuk; Kim, Dong Kwon (International Communications in Heat and Mass Transfer, 2024)
Herein, the free convection from vertically aligned tubes with curved extended surfaces is experimentally investigated. Heat transfer rates from tubes with curved extended surfaces to the ambient air are quantified under various conditions, including under varying tube wall temperatures, numbers of extended surfaces, and heights of extended surfaces in the radial direction. A correlation for calculating the Nusselt number is suggested, drawing upon the experimental findings. The difference between the experimental outcomes and the estimates generated by this correlation falls within a 10% margin. Using the correlation, a contour diagram is generated to show the thermal resistances across different numbers and thicknesses of extended surfaces. Finally, the thermal resistance of tubes featuring curved extended surfaces is evaluated against tubes with conventional straight extended surfaces. It is found that the tube with curved extended surfaces has a thermal resistance that is 20% less than that with straight extended surfaces.
Keywords: Ambient air; Condition; Curved extended surface; Extended surfaces; Heat transfer rate; Radial direction; Tube wall temperature; Vertical tube; Vertically aligned; Vertically aligned tube; Curved extended surfaces; Free convection; Vertically aligned tubes